2016
DOI: 10.19128/turje.77632
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de Teknolojik Pedagojik Alan Bilgisi Üzerine 2009-2013 Yılları Arasında Yapılan Çalışmalardaki Eğilimler

Abstract: analysis were analyzed by descriptive statistical methods such as percentage and frequency distributions in order to answer the research questions. According the findings; TPCK related studies in Turkey increased by year, pre-service teachers TPCK levels investigated more than teachers TPCK levels, the most preferred field is mathematics and science in the studies, quantitative methods were applied mostly, and surveys were used more than other data collection instruments. The analysis of the data obtained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Usta & Altun, 2017). The research(Dikmen & Demirer, 2016) supports this trend. 18% of the articles is based on technology integration into education, which is the second highest value.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Usta & Altun, 2017). The research(Dikmen & Demirer, 2016) supports this trend. 18% of the articles is based on technology integration into education, which is the second highest value.…”
supporting
confidence: 72%
“…Additionally, it is stated that the highest number of research done in Turkey between 2005 and 2013 are carried out with pre-service teachers (Baran & Canbazoglu Bilici, 2015). The national thesis and articles published between 2009 and 2013 revealed that 37% of the articles were about teacher candidates, 10% was about in-service teachers and 1% was about academicians (Dikmen & Demirer, 2016). The thematic analysis of the master thesis about TPACK between 2009 and 2019 showed 53.3% of the theses were about teacher candidates and 46.7% were about teachers (Çınar, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology knowledge increased distance education evaluation general level, technical level and learning process level. There are many studies in the literature on technological pedagogical content knowledge (Car & Aydos, 2020;Dikmen & Demirer, 2016;Gomleksiz, 2013;Gudek & Aciksoz, 2018;Kocak Usluel et al, 2015;Unal, 2013). In the articles examined in the TPACK studies reviewed by Korucu et al, (2017)., the education provided without TPACK and the education provided with TPACK support were compared, and the results were generally found that incorporating TPACK into teacher education would contribute to the academic success of teacher candidates; It has been concluded that technological pedagogical content knowledge and technology-related anxiety and stress have a negative relationship, that is, as TPACK increases, technological self-confidence will also increase.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…It has become a more important concept than the sum of the competencies that have (Dikmen & Demirer, 2016). When the components that make up the technological pedagogical content knowledge are examined, it is seen that there are seven different knowledge areas.…”
Section: Introductionmentioning
confidence: 99%